Magnificent Benito and his two front teeth - Rivera, Augie; Mike Rivera;Jason Moss (Quezon City, Philippines : Adarna House Inc., 2007)
Poor Benito was born with the largest set of two front teeth! Find out how his laughingstock turns out to be someone uniquely gifted.
Keywords: CHILDREN'S LITERATURE -- PHILIPPINES